Pendidikan dan Bimbingan Keagamaaan Berbasis Literasi Digital: Strategi Pemanfaatan Teknologi dalam Menanamkan Islam Moderat dalam Keberagamaan - Azwar Rahmat; Prio Utomo (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: In the digital era, online platforms influence religious discourse, making it crucial to integrate digital literacy into Islamic education to promote moderation and counter radical content, especially in diverse societies like Indonesia. Objective: This study aims to explore the role of technological advancements as a strategic approach to instilling moderate Islam in a diverse society through digital literacy-based Islamic education. Method: This research employs a literature study approach conducted in 2023. Data sources include both primary and secondary materials, collected through documentation and triangulation. Data analysis follows the stages of data reduction, data presentation, and conclusion drawing. Result: Fostering a moderate society requires promoting religious moderation through digital literacy, particularly for individuals unfamiliar with social media. Social media serves as an educational platform to enhance religious harmony by disseminating content that supports tolerance and coexistence. Conclusion: Moderate Islam emphasizes the importance of tolerance in maintaining religious harmony in everyday life. Digital literacy plays a crucial role in spreading religious moderation and fostering a balanced perspective in a diverse society. Contribution: This research contributes to the understanding of how digital literacy supports religious moderation and provides valuable insights for educators, policymakers, and religious leaders in utilizing technology for promoting religious harmony.